Odpowiedzi

2010-03-18T14:38:08+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9/:3
x=3
c)10=4-2x
-2x=10-4
-2x=6/:(-2)
x=-3
d)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
e)2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-t=7/:(-1)
t=-7
1 5 1
2010-03-18T14:39:16+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10 /(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9 /3
x=3
c)10=4-2x
10-4=-2x
6=-2x /(-2)
x=-3
d)2(x+1)=x
2x+2=x
x=-2
e)2t-(3t+1)=6
2t-3t-1=6
-t=7 /(-1)
t=-7
1 5 1
2010-03-18T14:39:24+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/:-5
x= 2

b)2x-2=7-x
2x+x=2+7
3x=9 /:3
x=3

c)10=4-2x
2x= 10-4
2x= 6/:2
x=3

d)2(x+1)=x
2x+2=x
2x-x=-2
x=-2

e)2t-(3t+1)=6
2t-(-3t) -1=6
5t-1=6
4t=6